2021
DOI: 10.1093/jpepsy/jsab095
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Experiences of Idiopathic Scoliosis in the Presurgical Period: A Qualitative Study

Abstract: Objective Adolescent idiopathic scoliosis (AIS) is a sideways curvature of the spine that can progress severely during adolescent development and require surgical intervention. This qualitative study was conducted to explore the psychosocial experiences of adolescents with idiopathic scoliosis during the presurgical stage of treatment. Methods Fourteen adolescents with moderate-to-severe AIS aged 12–17 years participated in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Adolescence, as a phase of impressionable personal and social reorganization, sees modulation of self-image reflective of this period of development 8. How physical appearance is conceptualized during this stage is context dependent with the results enfolding into adult identity 8–10. The burden of a physically apparent diagnosis, such as AIS, during this life stage has been modeled akin to chronic illness: cognitive adaptations, lifestyle changes, and disruptions away from the “norm” for peers their age 8.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence, as a phase of impressionable personal and social reorganization, sees modulation of self-image reflective of this period of development 8. How physical appearance is conceptualized during this stage is context dependent with the results enfolding into adult identity 8–10. The burden of a physically apparent diagnosis, such as AIS, during this life stage has been modeled akin to chronic illness: cognitive adaptations, lifestyle changes, and disruptions away from the “norm” for peers their age 8.…”
Section: Discussionmentioning
confidence: 99%
“…Wells’s “Personal perspective: moving out of pain,” 16 and West and Witt’s “A patient’s journey: bilateral developmental dysplasia of the hips” 17 both describe the demanding physical and mental aspects of recovery, the loss of a social life, loss of the ability to play with children, and the need for support from friends and family. West, a physician herself, closed by saying that as physicians, “we think we know how patients may feel and what they are worried about, [but] we really don’t.” Motyer et al 18 studied the psychological burden of living with adolescent idiopathic scoliosis. They found that patients struggled with emotions related to a fear of the operation and frustration about their inability to do the physical activities they enjoyed.…”
Section: Discussionmentioning
confidence: 99%
“…West, a physician herself, closed by saying that as physicians, "we think we know how patients may feel and what they are worried about, [but] we really don't." Motyer et al 18 studied the psychological burden of living with adolescent idiopathic scoliosis. They found that patients struggled with emotions related to a fear of the operation and frustration about their inability to do the physical activities they enjoyed.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, past research has demonstrated that most brace users feel different from their friends, and almost half endorse difficulty socializing with peers 48. In the interest of self-perception and peer conformity, many adolescents try to hide their brace wear from friends 11,49–51. Because adolescents with high self-esteem and strong peer relationships have already met their need for relatedness, they may be more likely to reject brace wear due to its potential negative impact on their preexisting social connections.…”
Section: Discussionmentioning
confidence: 99%